Participation and Learning Through the Lens of Transnational Comparative Studies - Schmidt-Lauff, Sabine (2022)
Participation in adult learning is shaped by “heterogeneous, complementary, antagonistic and contradictory temporalities” (Alhadeff-Jones, 2017, p. 3). Time is an essential, sociocultural factor, and learning needs and takes time (cf. Schmidt-Lauff, 2019). “Too busy at work” and “childcare or family responsibilities” (OECD, 2017) are the main reasons for non-participation in adult education. Time is a significant element in gender inequalities on the international level (European Institute for Gender Equality, 2020a, 2020c). This paper comparatively investigates how time, gender and learning are interwoven in adult education in Slovenia and Hungary. The analysis includes a first comparison of quantitative data and time-related policies. However, to do justice to the complex character of time, a triangular approach, using qualitative data collected in interviews with (non-)participants, goes beyond statistical description. The study aims to better understand the subjective experience of temporalities, while learning (considering stress and maturation, etc.). The paper seeks to raise awareness on the time sensitivity, for example, of struggling with temporal constraints when both caring for children and being a successful businessperson.